Pengaruh Kualitas Layanan Dan Penggunaan Digital Marketing Terhadap Keputusan Pembelian Jasa Pada Bengkel Las Jaya Mandiri Steel - Ade Oki Wagiman; Veta Lidya Delimah Pasaribu (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
Using quantitative methods, this research aims to determine and analyze the influence of service quality on service purchasing decisions, to determine and analyze the influence of the use of digital marketing on service purchasing decisions, and to determine and analyze the influence of service quality and the use of digital marketing on service purchasing decisions at the Jaya Mandiri Steel welding workshop, both partially and simultaneously. The sampling technique in this study uses a non-probability sampling technique, namely a saturated sample with a total of 72 respondents taken from all workshop consumers. Data analysis techniques used are: validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test, autocorrelation test, simple & multiple regression test, partial & simultaneous correlation coefficient test, partial & simultaneous determination coefficient test, T test and F test. Based on the results of the multiple linear regression test, the equation Y = 8.395 + 0.292X1 + 0.532X2 is obtained, indicating that the variables of service quality and the use of digital marketing have a positive coefficient on the purchasing decision variable. The value of the multiple regression coefficient of service quality is 0.292, indicating that service quality positively influences purchasing decisions, so that if service quality is increased by 1, it increases the value of purchasing decisions by 0.292 points. The multiple regression coefficient value of digital marketing usage is 0.532 indicating that the use of digital marketing positively influences purchasing decisions, so that if the use of digital marketing is increased by 1, it increases the value of purchasing decisions by 0.532 points. And the correlation value or R value of 0.845 and the R square value of 0.714 or 71.4% indicate a very strong relationship between service quality and the use of digital marketing on purchasing decisions. The F test results also produce a value of (85.944) > F table (2.750). This indicates that Ho3 is rejected and Ha3 is accepted. Therefore, it can be said that service quality and the use of digital marketing influence purchasing decisions.